2023
DOI: 10.3390/ijms241612583
|View full text |Cite
|
Sign up to set email alerts
|

Holothurian Wall Hydrolysate Ameliorates Cyclophosphamide-Induced Immunocompromised Mice via Regulating Immune Response and Improving Gut Microbiota

Abstract: Some biologically active compounds isolated from sea cucumbers stimulate the body’s immune response by activating immune cells. Immune function is closely related to the integrity intestinal barrier and balanced gut microbiota. However, it is unknown whether the daily administration of holothurian wall hydrolysate (HWH) ameliorated intestinal dysbiosis and barrier injury induced by immunodeficiency. This study aimed to investigate the immunomodulatory effect and the underlying mechanism of HWH in cyclophospham… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 78 publications
1
1
0
Order By: Relevance
“…29–31 As important immune organs, the spleen and thymus play crucial roles in regulating immune function. Consistent with the investigations of other researchers, 32–34 our current research indicated that CTX could decrease the body weight, spleen weight, and thymus weight in BALB/c mice, which indicated that CTX could cause damage to the immune system in the mice; however, the supplementation of BC encapsulated by liposomes improved these adverse alterations and exhibited a better effect than BC alone (Fig. 3 and 4).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…29–31 As important immune organs, the spleen and thymus play crucial roles in regulating immune function. Consistent with the investigations of other researchers, 32–34 our current research indicated that CTX could decrease the body weight, spleen weight, and thymus weight in BALB/c mice, which indicated that CTX could cause damage to the immune system in the mice; however, the supplementation of BC encapsulated by liposomes improved these adverse alterations and exhibited a better effect than BC alone (Fig. 3 and 4).…”
Section: Discussionsupporting
confidence: 91%
“…39 Detrimental environments can cause the oxidation and inflammation of the intestine, and numerous studies have indicated that CTX can induce a shortening and shedding of the intestinal villus, ultimately leading to damage of the intestinal mucosal layer. 32,33,40 Our current research suggested that CTX triggered damage to the jejunum structure, as manifested by the disappearance of muscle layers and exposure of the lamina propria structure; however, supplementation with BCL restored the structures of the jejunal epithelial cells (Fig. 6).…”
Section: Discussionmentioning
confidence: 64%